What disengages doctoral students in the biological and environmental sciences from their doctoral studies?. Issue 1 (2nd January 2017) - Virtanen, V.; Taina, J.; Pyhältö, K.
ABSTRACT: This study explored the causes of student disengagement from their doctoral studies in the biological and environmental sciences. The data came from interviews of 40 doctoral students (male = 15, female = 25) and underwent qualitative analysis for content. Our results showed that doctoral studies provide multiple contexts for disengagement, such as the scholarly community and supervision, while doctoral students' sense of distress, cynicism and inefficacy emerged as central components of disengagement. The study identified isolation, indifference, and lack of support and constructive feedback as sources of cynicism, while distress and inefficacy were more often related to failure or lack of progress in research. Our findings indicate that the source of disengagement can vary not only between individuals, but also between the academic activities at hand. Thus, while promoting an engaging doctoral experience, awareness of what typically triggers disengagement in the doctoral journey is vital.